2005
DOI: 10.1088/0305-4470/38/37/001
|View full text |Cite
|
Sign up to set email alerts
|

Damping of vortex waves in a superfluid

Abstract: The damping of vortex cyclotron modes is investigated within a generalized quantum theory of vortex waves. Similarly to the case of Kelvin modes, the friction coefficient turns out to be essentially unchanged under such oscillations, but it is shown to be affected by appreciable memory corrections. On the other hand, the nonequilibrium energetics of the vortex, which is investigated within the framework of linear response theory, shows that its memory corrections are negligible. The vortex response is found to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 19 publications
2
12
0
Order By: Relevance
“…We are only able to mention a couple of papers [18,19], that long ago reached the conclusion that the damping of vortex oscillations due to phonon scattering, should not modify appreciably the value of the friction coefficient calculated for a rigid vortex. The same conclusion was recently obtained for a high-frequency branch of helical waves, within a wider temperature range, including a roton-dominated regime [20].…”
Section: Introductionsupporting
confidence: 86%
See 3 more Smart Citations
“…We are only able to mention a couple of papers [18,19], that long ago reached the conclusion that the damping of vortex oscillations due to phonon scattering, should not modify appreciably the value of the friction coefficient calculated for a rigid vortex. The same conclusion was recently obtained for a high-frequency branch of helical waves, within a wider temperature range, including a roton-dominated regime [20].…”
Section: Introductionsupporting
confidence: 86%
“…[20], which has been shown to lead to a very good agreement with the experimental determinations of the longitudinal friction coefficient D for temperatures below 1 K [18]. From (15) we may see that B consists of two terms arising from the frequencies w w i = 0 and w i = W. Such contributions, however, are weighted by respective factors […”
Section: Mutual Friction In Helium Ii: a Microscopic Approachsupporting
confidence: 52%
See 2 more Smart Citations
“…Moreover, there are different theories [15,16,17] that yield several orders of magnitude higher values for the vortex mass, casting doubt on models based on massless vortices §. On the other hand, it has been recently suggested that an unambiguous vortex mass may not exist, and that ‡ Vortex bending in the form of thermal excitation of vortex oscillation modes, or collective excitations as Tkachenko waves are not expected to be relevant to this discussion [1,12,13]. § There have also been conflicting results for the vortex mass in superconductors [18].…”
Section: Introductionmentioning
confidence: 99%